Developing Teaching Materials of Academic Reading for Third Semester of English Department of Qomaruddin University - Lailatul Masruroh (Universitas Teuku Umar, 2022)
In learning activities, teaching materials play a critical role. Teaching materials have appealing designs that encourage students to learn and use them as a study resource. The goal of this study was to figure out and develop what kind of teaching materials are used in academic reading classes. This study employs the research and development technique, as well as the Borg and Gall models. There are ten stages of Borg and Gall models, but The author generates teaching materials in the fourth stage of Borg and Gall model only because the author wants to do this research fast; they are the production of initial drafts of materials for teaching. The type of materials of teaching from this research is handouts of academic reading, Academic reading was taught in the third semester of the English department of education faculty at the Qomaruddin University. So the subject of this research was students who are in semester three of the English Department of Qomaruddin University, some twenty-seven students consisting of twenty-two females and Five males. based on the findings of the development from teaching materials that have been already done. The Specific instructional objectives, instructional analysis, behavior analysis of learner, specific instructional objectives, and also syllabus are needed to create the handouts of teaching materials